(untitled) (Research, Society and Development, 2020)
The objective of this study is to present the clinical case of a 14-year-old male patient diagnosed with unicystic ameloblastoma in the posterior region of the right mandible involving dental elements 47 and 48. The lesion was discovered in a routine imaging exam for installation of an orthodontic appliance and after evaluation of the patient, who had no associated symptoms, a less invasive treatment was proposed, through biopsy, enucleation of the lesion and installation of a decompression device at the same surgical time. After confirmation through the histopathological report of ameloblastoma, the patient has been in outpatient follow-up for 2 years, presenting a satisfactory response to treatment, with bone regeneration in the area of ​​the defect and no complaints or signs of recurrence so far. Although there is no consensus on the best therapeutics for unicystic ameloblatoma, more conservative approaches have been shown to be effective in the treatment of young patients, thus allowing the maintenance of mandibular morphology and growth.